Analisis Tingkat Security Awareness Dalam Password Behavior Mahasiswa (Studi Kasus Mahasiswa FEBI UINSU Medan) - Fauzi, Muhammad Resty; Atika, Atika; Yanti, Nusantri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2024)
Analysis of security awareness in password behavior in mobile banking is very important to ensure the security of financial transactions through digital platforms. The purpose of this study is to analyze the level of security awareness in student password behavior, especially in the use of mobile banking. This type of research uses the Knowledge-Attitude-Behavior (KAB) model applied to the Human Aspects of Information Security Questionnaire (HAIS-Q) and the security awareness taxonomy of mobile users. The research data was collected using a questionnaire and received 61 valid respondents. The results of this study show that the level of information security awareness of users of banking service applications in Indonesia is at a sufficient level with a value of 70%. The value of each dimension of information security awareness is the knowledge dimension of 72% (sufficient), the attitude dimension of 69% (sufficient), and the behavior dimension of 69% (sufficient). This study successfully calculated the level of information security awareness of banking service application users. The final value of information security awareness obtained is 70% or at a sufficient level.